2007
DOI: 10.1080/10903120701536784
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Predictive Value of Paramedic Versus Emergency Physician Interpretation of the Prehospital 12-Lead Electrocardiogram

Abstract: Transmission to the ED for EP interpretation improves the PPV of the prehospital 12-lead ECG for triage and therapeutic decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 19 publications
0
42
2
Order By: Relevance
“…It is unclear if our results could be extrapolated to other EMS systems. Finally, the accuracy (75-80%) and sensitivity is below that previously reported in the literature 6,8 . A potential reason for this could be attributed to the simulated environment or due to the removal of the computer ECG interpretation.…”
Section: Limitationsmentioning
confidence: 72%
See 2 more Smart Citations
“…It is unclear if our results could be extrapolated to other EMS systems. Finally, the accuracy (75-80%) and sensitivity is below that previously reported in the literature 6,8 . A potential reason for this could be attributed to the simulated environment or due to the removal of the computer ECG interpretation.…”
Section: Limitationsmentioning
confidence: 72%
“…False activations by paramedics can lead to an increase in medical care costs and general mistrust by emergency physicians and cardiologists. Davis et al demonstrated that while paramedics are proficient at ECG interpretation, transmission of prehospital ECGs to Emergency physicians improves the positive predictive value of the ECG for therapeutic decision-making 6 . This study, combined with the growing body of literature suggests that leaders in out-of-hospital care should further investigate strategies to maximize prehospital provider accuracy in STEMI identification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25,33,36,47,48,53 Interventions of prehospital cardiac care were evaluated in five studies, and three studies investigated the impact of prehospital 12-lead electrocardiograms (ECGs). 26,27,30 One study investigated prehospital AMI diagnosis, 53 and a study evaluate protocol for percutaneous coronary intervention (PCI) bypass. 30 The majority of these studies demonstrate a positive correlation between DST and impact on patient assessment.…”
Section: Discussionmentioning
confidence: 99%
“…There could have been a risk that the volunteer group consisted of more interested and qualified personnel, and this may have influenced the results. In eight other studies, [26][27][28][29][30][31][32][33] the intervention was compared with a retrospective control group. They all also demonstrated a significant favor toward the intervention group, but it is difficult to determine if the two compared groups were homogeneous enough to draw any conclusions.…”
Section: Excluded Studiesmentioning
confidence: 99%